On the run in their own country: Political and institutional challenges in the context of internal displacement - Anne Koch (Stiftung Wissenschaft und Politik (SWP), 2020)
Although cross-border flight has been high on the international agenda for several years, the more wide-spread phenomenon of internal displacement has received scant political attention, despite the fact that it promotes conflict and hinders development. The problem is exacerbated when internal displacement continues over an extended period. If a large population group is denied the ability to exercise its basic as well as its civil rights for years, there are high costs and political risks for society as a whole. Internal displacement can have many causes. If it becomes a protracted phenomenon, this points to fundamental political shortcomings. Hence, the issue is a politically sensitive matter for the governments concerned, and many of them consider offers of international support as being undue interference in their internal affairs. At the global and regional levels, legislative progress has been made since the early 2000s. However, the degree of implementation is still inadequate and there is no central international actor to address the concerns of IDPs. The political will of national decision-makers is a prerequisite for the protection and support of those affected. This can be strengthened if governments are made aware of the negative consequences of internal displacement and if their own interests are appealed to. The German government should pay more attention to the issue of internal displacement and make a special effort to find durable solutions. The most important institutional reform would be to reappoint a Special Representative for IDPs who would report directly to the UN Secretary-General.
Keywords: 320